Study on the Effects of Enzymatic Hydrolysis on the Physical, Functional and Chemical Properties of Peanut Protein Isolates Extracted from Defatted Heat Pressed Peanut Meal Flour (Arachis hypogaea L.) - Kain, Regena Juliana; Chenc, Zhengxing; Abu-Kpawoh, John Christian (Pakistan Journal of Nutrition, 2009)
Physical, chemical and functional properties of peanut protein isolates (HPI) and hydrolysis (HPH) extracted from peanut meal obtained from heat treated peanut oil extraction method were analyzed. HPH exhibited superior functional properties such as whipping, emulsification, fat and water absorption properties. Thermal denaturation profiles indicate that there is no significant difference (p<0.05) between HPI and HPH at both onset and transition temperatures. However, the conclusion temperatures were found to be significantly different (p<0.05). Protein solubility was pH dependent with HPH been more soluble at all pH levels. However, solubility was low at the isoelectric pH range of 4.5-5.5. Electrophoretic patterns obtained from SDS-PAGE show that HPH registered a lower molecular weight (<31KDa) compared to HPI (<66 KDa). HPH had relatively smaller particle sizes (±0.1 μm) compared to HPI (±100 μm). Protein isolates extracted from peanut meal obtained from cold pressed peanut oil extraction method were used as control in analyzing functional parameters but HPH still exhibited superior qualities. Both HPH and HPI were found to be nutritionally rich in most essential amino acids with respect to the recommended FAO/WHO amino acid requirement patterns for both adults and children.